2020
DOI: 10.1089/ham.2020.0173
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor: COVID-19 Infections Do Not Change with Increasing Altitudes from 1,000 to 4,700 m

Abstract: C oronavirus disease (COVID-19) infection, after the first case reported in Wuhan, China, on December 31, 2019 and declared a pandemic by the World Health Organization in March 2020, has climbed by September 2nd to 26,076,572 cases and 864,162 deaths worldwide.Although it has been suggested that living at high altitude could decrease the rate of coronavirus transmission and mortality from COVID-19 (Arias-Reyes et al., 2020), new studies have not confirmed this protective effect. In fact, the case-fatality rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 4 publications
1
10
0
3
Order By: Relevance
“…When all altitudes (2-4700 m) are assessed in a single analysis, an inversely proportional correlation with altitude is observed as reported in other studies (Castagnetto et al, 2020;Segovia-Juarez et al, 2020). This relationship is apparently an artifact as only this negative correlation is evident at altitudes between 0 and <1500 m. From 1500 to 4700 m, no association of positive cases with altitude is observed even though variables such as partial oxygen pressure, humidity, solar and cosmic radiation and humidity, and production of vitamin D change proportionally as altitude increase (Pun et al, 2020); further production of the angiotensin 2-converting enzyme, a carrier molecule for the entry of SARS-CoV-2 virus into the host cell, has also been suggested (Millet et al, 2021;Srivastava et al, 2020).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…When all altitudes (2-4700 m) are assessed in a single analysis, an inversely proportional correlation with altitude is observed as reported in other studies (Castagnetto et al, 2020;Segovia-Juarez et al, 2020). This relationship is apparently an artifact as only this negative correlation is evident at altitudes between 0 and <1500 m. From 1500 to 4700 m, no association of positive cases with altitude is observed even though variables such as partial oxygen pressure, humidity, solar and cosmic radiation and humidity, and production of vitamin D change proportionally as altitude increase (Pun et al, 2020); further production of the angiotensin 2-converting enzyme, a carrier molecule for the entry of SARS-CoV-2 virus into the host cell, has also been suggested (Millet et al, 2021;Srivastava et al, 2020).…”
supporting
confidence: 82%
“…They suggest that the reported lower incidence and mortality of COVID-19 in high-altitude places observed by others (Stephens et al, 2021) remain to be confirmed. Stephens et al (2021) study two groups: one living in counties located at altitudes less than 914 m and the other at altitudes higher than 2133 m. Castagnetto et al (2020) assessing data at district level have demonstrated that at different altitude ranges from 0 to <1000 m, 1000 to 2500 m, and 2500 to 4700 m in Peru, the negative association with altitude was observed only in the group ranging from 0 to <1000 m. If analysis is done using all altitudes from 0 to 4700 m a negative association is observed between altitude and cases with SARS-CoV-2. Fernandes et al (2021) assessing 154 cities in Brazil located between 5 and 1135 m. They observe a negative association between altitude and cases of SARS-CoV-2.…”
mentioning
confidence: 99%
“…A study published early in the pandemic reported that COVID-19 had a lower impact on inhabitants of high-altitude areas in Asia and South America than of lowlands (Arias-Reyes et al, 2020 ). The hypothesis that high altitude populations are protected from severe effects of COVID-19 through a superior response to hypoxemia has been proven to be wrong (Castagnetto et al, 2020 ; Intimayta-Escalante et al, 2020 ; Joyce et al, 2020 ; Pun et al, 2020 ).…”
Section: Impact Of the Pandemic In Mountainous Areasmentioning
confidence: 99%
“…At altitudes between 1,000 and 4,700 m, there was no significant association between altitude and incidence of infection. 4 An altitude gradient for protection against SARS-CoV-2 contagion could not be demonstrated.…”
mentioning
confidence: 99%